Enhancing the Efficacy of Tumor Vaccines Based on Immune Evasion Mechanisms - Chen, Jianyu; Zhang, Honghao; Zhou, Lijuan; Hu, Yuxing; Li, Meifang; He, Yanjie; Li, Yuhua (Frontiers in Oncology, 2021)
Tumor vaccines aim to expand tumor-specific T cells and reactivate existing tumor-specific T cells in dormant or unresponsive state. As such, there are growing interests in improving the durable anti-tumor ability of tumor vaccines. Failure of vaccine-activated T cells to protect against tumors is thought to be the result of immune escape mechanisms of tumor cells and intricate immunosuppressive tumor microenvironment. In this review, we discuss how tumor cells and tumor microenvironment influence the effect of tumor infiltrating lymphocytes and summarize the way to improve the efficacy of tumor vaccines by improving the design of current tumor vaccines and combining tumor vaccines with other therapies, such as metabolic therapy, immune checkpoint blockade immunotherapy and epigenetic therapy.